p-Methylisonitrosoacetophenonehydrazone as an Extractive Agent for the Spectrophotometric Determination of Nickel(II) - lokhande, R.S.; Jaywant, A.S. (Asian Journal of Chemistry, 2010)
A simple and rapid extractive spectrophotometric method for the determination of Ni(II) is described. The complex formed between Ni(II) and p-methylisonitrosoacetophenonehydrazone is extracted into chloroform from aqueous solution at pH 7.5. The extracted species has an absorption maxima at 480 nm and obeys Beer's law over a range of 0.2-20 μg mL–1 of Ni(II); the molar absorptivity being 4.87 x 103 L mole–1 cm–1. Interference from the foreign ions has also been studied.